2008
DOI: 10.2139/ssrn.1317342
|View full text |Cite
|
Sign up to set email alerts
|

Administrative and Judicial Enforcement in Consumer Protection: The Way Forward

Abstract: This text may be downloaded for personal research purposes only. Any additional reproduction for other purposes, whether in hard copy or electronically, requires the consent of the author(s), editor(s). If cited or quoted, reference should be made to the full name of the author(s), editor(s), the title, the working paper or other series, the year, and the publisher. The author(s)/editor(s) should inform the Law Department of the EUI if the paper is to be published elsewhere, and should also assume responsibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 39 publications
1
16
1
2
Order By: Relevance
“…Although these directives have narrowed the Member States' available options for setting their own consumer policy, they still leave some possibilities for the Member States to go further in their national level of consumer protection. Consequently and notwithstanding the efforts of the European Commission to align consumer protection in the Member States, current research has shown that national consumer policy approaches still differ (Cafaggi and Micklitz 2009;Repo and Timonen 2017;Wind 2016).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Although these directives have narrowed the Member States' available options for setting their own consumer policy, they still leave some possibilities for the Member States to go further in their national level of consumer protection. Consequently and notwithstanding the efforts of the European Commission to align consumer protection in the Member States, current research has shown that national consumer policy approaches still differ (Cafaggi and Micklitz 2009;Repo and Timonen 2017;Wind 2016).…”
mentioning
confidence: 99%
“…Comparative studies of consumer policy in Europe have used a regime approach in seeking to identify similarities and differences of consumer policy models between groups of countries (Cafaggi and Micklitz 2009;Cseres 2005;Micklitz 2003;Repo and Timonen 2017;Trumbull 2006a, b). Despite different research interests and scientific perspectives, all of these studies found consumer policy regimes, such as a Scandinavian regime consisting of Denmark, Finland, and Sweden or an East European regime consisting of all East European Member States.…”
mentioning
confidence: 99%
See 3 more Smart Citations